Relation between Liver Transaminases and Dyslipidaemia among 2-10 y.o. Northern Mexican Children. - Maria Del Mar Bibiloni; Rogelio Salas; Georgina M Nuñez; Jesús Z Villarreal; Antoni Sureda; Josep A Tur (PLoS ONE)
Background and aims The increase in overweight and obese children may be linked to increased rates of liver damage and dyslipidaemia. This study aimed to explore the associations of liver biomarkers with overweight/obesity and dyslipidaemia in Mexican children. Methods The study was a population-based cross-sectional nutritional survey carried out in the State of Nuevo León, Mexico. The study included a 414 subjects aged between 2 and 10 years old (47.8% girls) who took part in the State Survey of Nutrition and Health-Nuevo León 2011/2012. Associations between alanine aminotransferase (ALT) and aspartate aminotransferase (AST), ALT/AST ratio, and major components of serum lipid profile were assessed. Results Children with high ALT (defined as ≥P75) showed higher prevalence of dyslipidaemia than their counterparts, with high prevalence of high TChol (P = 0.053), non-HDL-chol, TG, and low HDL-chol. Children with an AST/ALT ≥T3 ratio were 0.43-times (95% CI: 0.25-0.74) and 0.27-times (95% CI: 0.17-0.44) low likely to be overweight/obese and to have dyslipidaemia than those with an AST/ALT <T1 ratio, respectively. The risk of high TChol, LDL-chol, non-HDL-chol and TG, and low HDL-chol levels also decreased in AST/ALT ratio groups. Conclusions Our results pose the need for further investigation on whether AST/ALT may be useful as screening test in the assessment of children with cardiometabolic risk.